INFLUENCE OF LUNAR CYCLES ON ANTHOCYANIN CONTENT OF JUSTICIA WYNAADENSIS ADENSIS ADENSIS (NEES) HEYNE EX T. AND. - M.VASUNDHARA; R. PRIYANKA; M. NETHRAVATHI; MANJUNATH SWAMY (The Bioscan, 2018)
Anthocyanins are the most abundant naturally occurring flavonoid pigments and a group of antioxidants known for their therapeutic use. In humans and other mammals, an internal mechanism or the biological clock, imposes circadian rhythms on physiological, biochemical and molecular events. While plants, are unique, their control mechanism is external, specifically the environment. Light has shown to be the most important environmental factors influencing anthocyanin biosynthesis in plants. The present study was established to understand the effect of lunar cycles on the anthocyanin pigment of Justicia wynaadensis under Bangalore condition. The results clearly demonstrated the effect of Full moon and new moon days on the accumulation of pigment. The results reported that the leaves collected on New moon day (2nd August, 2016) recorded highest accumulation of anthocyanin pigment of 11.31mg/L. The content gradually decreased from 11.31 mg/L to 0.488 mg/L, while, on Full moon day, the content reduced from 7.3mg/L to 1.428mg/L. The lunar cycles, thus play a predominant role in the accumulation of the pigment. Justicia wynaadensis can be considered as a natural antioxidant and as a food supplement in prevention diseases and to stay healthy throughout the year.